Internal conflicts in Myanmar transnational consequences - V.R. Raghavan (Vij Books India, 2011)
In the recent years, the interstate wars have declined and intrastate wars/ internal conflicts are on rise. Impacts of internal conflicts are no longer limited within a nation state, they incur international consequences of disturbing magnitude. Myanmar (Burma) is affecled by two types of internal conflicts. The first is between the military government and various ethnic groups spread along the international borders with India. China, Laos and Thailand. These ethnic minorities speak different languages, have different cultures and have taken up arms. They seek to have a say in the political process, economic development of their regions and the right to practice their language, culture and religion without constraints.